Perilaku Keuangan Mahasiswa Penerima Kip-Kuliah: Ditinjau Dari Pengetahuan, Sikap, Dan Locus Of Control - Hisa, Yuli Lisniangsi; Astaginy, Niar; Kumalasari, Fitri (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the influence of financial knowledge and financial attitudes on financial behavior, with locus of control as a moderating variable, among KIP-K scholarship recipients at the Faculty of Social and Economic Sciences, Universitas Sembilanbelas November Kolaka. A quantitative approach was employed, with data collected through questionnaires. The respondents consisted of 182 KIP-K recipient students. The research instrument was tested for validity and reliability using SPSS 25.0. Data analysis was conducted using the Structural Equation Modeling (SEM) approach with SmartPLS 4.0. The results of the study indicate that financial knowledge, financial attitudes, and locus of control have a positive and significant effect on financial behavior. However, locus of control does not moderate the relationship between financial knowledge and financial attitudes on financial behavior.